INVESTIGASI PENGETAHUAN SWAMEDIKASI MENGGUNAKAN ANALGETIKA PADA LANSIA DI KOTA BENGKULU - Yona Harianti Putri; Reza Rahmawati; Dwi Dominica (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problems: Pain affects the lives of at least 10% of the world's population of about 60 million people. The Central Statistics Agency of Bengkulu Province said that in 2019 the response of the elderly to the health complaints they experienced in Bengkulu Province was self-medicating, outpatient treatment, and a combination of both. The Aim Of The Research: This study aimed to investigate the knowledge of self-medication using analgesics. Research Method: This descriptive observational study was performed on the elderly population in Bengkulu City. Data were collected by a researcher-made self-medication questionnaire. The total sample in this study was 400 respondents. The Result: The results obtained in this study were the elderly who did self-medication of analgesics were 51.5% women and 48.5% men. Conclusions: In this study regarding the level of self-medication knowledge, it was found that only 40% of the elderly knew the name of the drug, only 13.2% of the elderly knew the dose of the drug, and 6.2% of the elderly knew the side effects of the drug. Keywords: Elderly, Analgesic, Self-Medication